Developing A Culturally Responsive Reading Module For First-Grade Islamic Junior High School Students - Rahman, Arif; Wahyudiantari, Ni Wayan Prami; Sugianto, Riris (Universitas Pendidikan Mandalika, 2024)
Reading instruction plays a fundamental role in shaping students' academic success, particularly in culturally diverse contexts. In Islamic educational institutions, there is a critical need for materials that resonate with students' cultural and religious backgrounds. This study aimed to develop a culturally responsive reading instructional module tailored to the specific needs of first-grade students at an Islamic Junior High School in Mataram, Indonesia. Grounded in constructivist learning theory, which emphasizes the importance of contextual relevance in education, the study integrates Islamic cultural and religious themes to foster student engagement and improve reading comprehension. A mixed-methods approach was utilized, involving surveys, interviews, and pre- and post-assessments. The study included 60 first-grade students and their teachers. The results demonstrated significant improvements in students’ reading comprehension and engagement. The mean test scores increased notably, and students expressed higher levels of enjoyment with the culturally aligned materials. These findings underscore the importance of integrating cultural and religious content into instructional materials, creating more inclusive and effective educational experiences. The study offers practical insights for educators in similar settings, highlighting the potential of culturally responsive pedagogy to bridge the gap between students' home and school environments, while also fostering a deeper appreciation of their cultural heritage. This contribution provides valuable guidance for the future development of culturally tailored educational strategies in Islamic contexts.